Clergywomen's experience of ministry in the Church of England. Issue 8 (17th November 2018) - Robbins, Mandy; Greene, Anne-marie
Abstract: The ordination of clergywomen within the Church of England in 1994, and more recently the consecration of women as bishops has generated significant public interest. This paper explores the clergywomen's understanding of their ministry in light of these changes. This study explores the stories of twenty-one clergywomen in the Church of England who have served, or are currently serving, in stipendiary parochial ministry. Their ages range from twenty-nine years to sixty-three. Four were among the first to be ordained priest in 1994 and seventeen were ordained between 1996 and 2009. This study employs thematic analysis to enable insights into these women's understanding of their experience of ministry. Three latent themes emerged from the data: perceptions of difference between explicit and implicit opposition; differences in how their ministry is perceived by others; and tensions in ministry between their internal and their external worlds.